Listening in Sacred Spaces: The Sanctuary of Poseidonia and Selinunte’s Main Urban Sanctuary - Bellia Angela (Open Archaeology, 2023)
The aim of this work is to analyse recent studies which have raised new hypotheses concerning aural architecture as an emerging trend in humanities research, with a particular focus on the intersection of sacred space, rituals, and sound in the past. These studies have highlighted how sacred buildings not only defined a sacred place as a physical and symbolic expression of a specific form of worship but also established the setting for performative and multisensorial ceremonies in which music, dance, and other sonic events played an important role. In this contribution, we investigate studies on aural architecture to explore if the location of sacred spaces indicates whether ancient people reacted to ritual and musical developments by modifying sanctuaries or by designing and constructing new buildings and spaces for performances. In addition, this article explores studies on aural architecture to obtain an overview of how specific sonic features could have influenced the soundscape of sacred spaces, which consisted not only of songs, music, prayers, recitations and religious sonic and vocal utterances but also of natural elements, such as animals, water, and wind. This overview also takes into consideration how digital technologies and virtual acoustics can help shape our understanding of the architecture-sound nexus.